PERBANDINGAN JOB MIX DESIGN BETON ANTARA METODE DoE DAN ACI - Arifal Hidayat (Jurnal APTEK, 2014)
The purpose of this study was to compare the results of the design (theoretical) mix concrete plan fc' of 22.5 MPa for 1 m3 using the Department of Environment (DoE) and the method of the American Concrete Institute (ACI), of both methods will be known theoretically - use of materials optimal material (economical). Stages in the concrete mix design fc ' of 22.5 MPa are : (1) sieve analysis of fine aggregate and coarse aggregate, (2) examination of specific gravity and absorption of fine aggregate and coarse aggregate, (3) a weight check aggregate content and (4) examination of sludge levels using the same material that is derived from the aggregate quary Tanjung district of Rokan Hulu. Berdasarkan complicated the analysis and discussion concluded that the concrete mix design method of ACI produces a mixture proportion of material that is relatively less when compared to using DoE methods. This means that in practice the design of concrete mix ACI method is more economical in terms of the use of materials on using DoE methods.